The Impact of Anabolic Androgenic Steroids on Organ Failure in Bodybuilders - a Review of Actual Literature - Marcinkowska, Julia; Muras, Mateusz Szymon; Lorenc, Tomasz; Michalik, Maciej; Marcinkowski, Krzysztof; Mikszta, Jakub; Mikszta, Natalia (Quality in Sport, 2025)
Anabolic-Androgenic Steroids (AAS), despite their therapeutic applications in the management of selected medical conditions, are increasingly being misused for non-medical purposes—particularly among bodybuilders and individuals seeking to enhance their physique. This review article examines the impact of chronic AAS administration on the functionality of selected human organs and physiological systems. Based on current clinical and preclinical evidence, the biological mechanisms of AAS action are discussed, with particular emphasis on their affinity for androgen receptors and modulation of intracellular signaling pathways. The paper presents robust evidence of the adverse effects associated with AAS use, including cardiomyopathies, renal dysfunction, neuropsychiatric disorders (notably increased aggression and depressive symptoms), hepatotoxicity, and metabolic disturbances. Special attention is given to the potential mechanisms underlying AAS-induced toxicity, as well as the reversibility of the observed pathological alterations. The findings underscore the necessity for intensified health education and systematic monitoring of individuals using AAS, due to the elevated risk of irreversible, multisystem complications.